ZEA mediates autophagy through the ROS-AMPK-m-TOR pathway to enhance the susceptibility of mastitis induced by Staphylococcus aureus in mice - He, Yuhong; Su, Niri; Yang, Hengyi; Yang, Wencheng; Zhao, Caijun; Fu, Yunhe; Hu, Yubo; Hu, Xiaoyu (Ecotoxicology and environmental safety, 2023)
Mastitis is an inflammatory response of the mammary tissue caused by pathogenic bacterial infections, especially Staphylococcus aureus (S. aureus). Zearalenone (ZEA) is one of the common mycotoxins in moldy feed, which usually affects the cow's resistance to pathogenic microorganisms. However, it is not well understood whether ZEA affects the development of mastitis. Therefore, this study aimed to investigate the role of ZEA in the development of S. aureus-induced mastitis in mice. The results showed that administered daily by gavage for one week of ZEA (40 mg/kg) aggravated the severity of mastitis induced by S. aureus. Furthermore, we found that ZEA promotes the adhesion and invasion of S. aureus into mouse mammary epithelial cells (MMEC) by activating autophagy, and the activation of autophagy mediated by ROS-AMPK-m-TOR pathway. Taken together, the results showed that ZEA enhances S. aureus-induced mastitis susceptibility through activating autophagy mediated by ROS-AMPK-mTOR signaling pathway. [Display omitted] •Zearalenone as a major fungal toxin with serious affects for dairy development.•Zearalenone activates the ROS-AMPK-mTOR pathway to induce autophagy.•Zearalenone dose-dependently enhances the susceptibility of Staphylococcus aureus.•Inhibition of autophagy reduces susceptibility to Staphylococcus aureus.